Pathways to antisocial behavior: a framework to improve diagnostics and tailor therapeutic interventions - De Wit-De Visser, Brenda; Rijckmans, Madeleine; Vermunt, Jeroen K.; van Dam, Arno (Frontiers in Psychology, 2023)
The Antisocial Personality Disorder (ASPD), and antisocial behavior in general, is associated with significant impact on individuals themselves, their environment, and society. Although various interventions show promising results, no evidence-based treatments are available for individuals with ASPD. Therefore, making informed choices about which treatment can be applied to an individual patient is complicated. Furthermore, contradictory findings on therapy effectiveness and underlying factors of antisocial behavior, such as cognitive impairments and personality traits, fuel the debate whether the conceptualization of ASPD in the DSM-5 is accurate and whether this population can be seen as homogenous. A conceptual framework, based on the reciprocal altruism theory, is presented in which we propose different pathways to antisocial behavior. These pathways suggest underlying dynamics of antisocial behavior and provide an explanation for previous contradictory research outcomes. This framework is intended to serve as a clinically relevant model that provides directions for improving diagnostics and matching treatments to underlying dynamics in the antisocial population.